1999
DOI: 10.1056/nejm199905203402002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Therapy for Calcific Tendinitis of the Shoulder

Abstract: In patients with symptomatic calcific tendinitis of the shoulder, ultrasound treatment helps resolve calcifications and is associated with short-term clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
20

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(117 citation statements)
references
References 20 publications
0
97
0
20
Order By: Relevance
“…6) and no re-injury was reported. Myositis ossificans prevention in this case can be explained by the overlap of the treatment phases, including early stretching and strengthening 13,16) , active cycling, and use of therapeutic ultrasound (US) 32,33) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6) and no re-injury was reported. Myositis ossificans prevention in this case can be explained by the overlap of the treatment phases, including early stretching and strengthening 13,16) , active cycling, and use of therapeutic ultrasound (US) 32,33) .…”
Section: Discussionmentioning
confidence: 97%
“…Although there is no promising animal or clinical evidence that US can help repair muscle injuries [20][21][22][23] , there is plenty of evidence showing the effects of US in collagen repair and re-synthesis 25,[33][34][35][36][37][38][39][40][41] . The use of US in the present clinical case was oriented at improving muscle collagen extracellular matrix (CEM) repair, based upon US effects on fibroblast proliferation and collagen synthesis 25,39) .…”
Section: Discussionmentioning
confidence: 99%
“…The predisposition to spontaneous resorption of the deposit [10,11] cannot guide the therapy: waiting for the spontaneous vanishing of the calcification could lead to important painful limitations of function [12]. Conservative attitudes give fair short-term outcomes [9,13,14], but in the long-term follow-up they lead to less encouraging results [5]. In the literature, few authors reported satisfying results in patients treated with shock-wave therapy for calcifying tendinitis of the shoulder, with improvement of symptoms and function.…”
Section: Discussionmentioning
confidence: 99%
“…The tip of the applicator was placed at the highest point of pain using a common gel ultrasound to couple the applicator to the skin. All patients were evaluated before treatment and after 10 weeks (range, [8][9][10][11][12][13][14][15] by radiography, sonography and a patient-oriented questionnaire: the Dawson shoulder questionnaire, validated Italian version [6]. The Dawson shoulder questionnaire consists of 12 questions with 5 multiple-choice responses, from 1 (best) to 5 (poorest), which investigates the severity of symptoms and function.…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by the deposition of hydroxyapatite crystals that principally affects the tendons of the rotator cuff (2) , and the tendon of the supraspinatus often the most affected (3) . Its etiology is controversial and it has been suggested that a local hypo vascularization of Codman in the tendon of the supraspinatus is responsible for initiating the degenerative process, which subsequently leads to calcification (4) .…”
Section: Introductionmentioning
confidence: 99%